Korelasi antara Kadar Insulin dalam Darah dengan Kekuatan Otot Tangan Kanan dan Kiri pada Kelompok Lanjut Usia - Kosasih, Robert; Frisca Frisca; Santoso, Alexander Halim; Destra, Edwin; Gunaidi, Farell Christian; Jap, Ayleen Nathalie; Gracienne Gracienne (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Muscle strength is the ability of muscles to produce power for physical activity, important for mobility, balance and body function. Decreased muscle strength, especially due to aging, negatively impacts quality of life and increases the risk of diseases such as diabetes and cardiovascular disease. Handgrip is a simple method for measuring muscle strength, especially hand grip strength. This study aims to evaluate the relationship between hand grip strength and blood insulin levels in the elderly. This study used a cross-sectional design at the Bina Bhakti Nursing Home with 93 participants aged 60 years and over. Hand grip strength was measured using a dynamometer, and blood insulin levels were measured from venous blood samples. Data were analyzed using Spearman correlation. The results showed an average right hand grip strength of 10.23 kg and left hand 9.33 kg, with an average blood insulin level of 4.83 µU/mL. A significant positive correlation was found between right and left hand grip strength (rho = 0.884, p < 0.001), as well as between right (rho = 0.218, p = 0.036) and left hand grip strength (rho = 0.290, p = 0.005) and insulin levels. blood. These results indicate that hand grip strength can be an indicator of metabolic health in the elderly. Interventions such as strength training and proper nutrition are important for maintaining muscle strength and metabolic health in the elderly.